PERBEDAAN KINERJA KUALITAS LAYANAN KARYAWAN RESTORAN SEDERHANA DAN NASI KAPAU PADA KAWASAN WISATA KULINER THE VITKA CITY COMPLEX - Asman Abnur; Agung Edy Wibowo (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
The success of providing satisfaction to customer with, is to fit up what the customer looking at benefits which company has provided them. Success in culinary business management does not only depend on the menu offered but also on the packages delivered to customers, namely service of quality. The service quality factor in a culinary business of course related to the workforce or employees. It means that the employee must be having a better performance, because the culinary business is a kind of services business. Today, many business sectors affected by the presence of Covid-19. As a precautionary measure due to the COVID-19 pandemic. Several restaurants have offered a choice of dining services that can be reached by consumers, one of which is the existence of a Nasi Kapau restaurant. Nasi Kapau is a management choice strategy in serving consumers. Restaurant Nasi kapau is a new phenomenon in Batam, this restaurant always crowded with many customers in a long line. Saturation sampling was used in this research with 38 samples counted and processed. The result of this test show that; There is a significant difference in performance between employees of a Sederhana restaurant and a Nasi Kapau restaurant